Tools for Decreasing Ambiguity and Increasing Clarity. - Mockaitis | How to Be Awesome at Your Job, Pete (linkedin.com, 2023)
Learn how to communicate more clearly in life and at work—including words to avoid, ways to convey your message, and questions you can ask to reveal what others truly think.